Priorities for Public Sector Research on Food Security and Climate Change, Review 2 by Melinda Sundell - Sundell, Melinda (2013)
Priorities for Public Sector Research on Food Security and Climate Change, Review 2, Melinda Sundell, Stockholm Environment Institute. Presented at the Food Security Futures Conference in Dublin, Ireland on 12 April 2013.